Perspectives of clinical handover processes: a multi‐site survey across different health professionals. Issue 1 (28th September 2015) - Manias, Elizabeth; Geddes, Fiona; Watson, Bernadette; Jones, Dorothy; Della, Phillip
Abstract : Aims and objectives: To examine the perspectives of health professionals of different disciplines about clinical handover. Background: Ineffective handovers can cause major problems relating to the lack of delivery of appropriate care. Design: A prospective, cross‐sectional design was conducted using a survey about clinical handover practices. Methods: Health professionals employed in public metropolitan hospitals, public rural hospitals and community health centres were involved. The sample comprised doctors, nurses and allied health professionals, including physiotherapists, social workers, pharmacists, dieticians and midwives employed in Western Australia, New South Wales, South Australia and the Australian Capital Territory. The survey sought information about health professionals' experiences about clinical handover; their perceived effectiveness of clinical handover; involvement of patients and family members; health professionals' ability to confirm understanding and to clarify clinical information; role modelling behaviour of health professionals; training needs; adverse events encountered and possibilities for improvements. Results: In all, 707 health professionals participated (response rate = 14%). Represented professions were nursing (60%), medicine (22%) and allied health (18%). Many health professionals reported being aware of adverse events where they noticed poor handover was a significant cause. Differences existed between health professions in terms of how effectively they gave handover, perceived effectiveness of bedside handover vs. nonbedside handover, patient and family involvement in handover, respondents' confirmation of understanding handover from their perspective, their observation of senior health professionals giving feedback to junior health professionals, awareness of adverse events and severity of adverse events relating to poor handovers. Conclusions: Complex barriers impeded the conduct of effective handovers, including insufficient opportunities for training, lack of role modelling, and lack of confidence and understanding about handover processes. Relevance to clinical practice: Greater focus should be placed on creating opportunities for senior health professionals to act as role models. Sophisticated approaches should be implemented in training and education.